Journalists as First Responders - Rupar, V (Taylor & Francis, 2020)
Covering terrorist attacks has posed numerous challenges to mainstream media across the world. Bringing information to the public quickly remains a primary goal for news media, but the journalistic duty to tell the truth comes with an increased responsibility for the accuracy of reports. When news is broken by civilian eyewitnesses and is posted by social media before it has even gone through the barest of verification checks, news media editors struggle to fulfil the task of informing the public while reporting on stories that hold the potential to alarm the audience. This paper offers some insights into the ways the New Zealand news media organised reporting on the March 15th terrorist attack in Christchurch. Based on face-to-face interviews with selected editors of major news organisations in New Zealand, it investigates the ways they operated in this situation. It explores key moments in editorial decision making on 15 March 2019, the first day of coverage of the terrorist attack. It focuses on the ‘first responder’ elements of news media work – speed and accuracy in providing information about the mosque attacks – to identify how journalistic norms are adapted and changed to report this breaking news.
Keywords: Journalism; Terrorist attack; First responders; Christchurch; Editorial decisions